Association Between Cholesterol and Low-Density Lipoprotein Levels with In-Hospital Complications of Percutaneous Coronary Intervention - Hemn Jamal Jamil; Amanj Abubakir Xaznadar (Advanced Medical Journal)
Background and objectives: Percutaneous coronary intervention is the treatment of choice for revascularization in patients with coronary artery disease. The aim of the study is to investigate the relationship between cholesterol and low-density lipoprotein levels and percutaneous coronary intervention complications.